PENYULUHAN PENCEGAHAN STUNTING PADA ANAK DI SD NEGERI 060919 - Tarigan, Juliyanti; Syahrir, Lesmana; Tiji, Wijaya Taufik; Simangunsong, Batara; Pasaribu, Sumihar M.R.; Gea, Melfan J.; Harianja, Ester G.; Tampubolon, Gelberd V.M.; Simalango, Penina T.; Ginting, Lucky A.B.; Sibuea, Charina T.Y.; Pangaribuan, Megaria Evhiphanias; Simanullang, Yolanda K.H.R.; Ginting, Mischkel A.; Meha, Panahian M. (Jurnal Pengabdian Pada Masyarakat METHABDI, 2023)
Stunting is a situation where a child's height is stunted compared to the height of children his age. In Indonesia, stunting is a problem in the health sector that is still high. This condition occurs because children are malnourished for a long time with signs of failure in the child's growth and development (growth faltering) which starts from pregnancy until the child is 2 years old. This is the formulation of our problem in holding outreach activities on the topic of Stunting at SD Negeri 060919, Kec. Medan Sunggal, Medan city. This article was created with the aim of providing education and information regarding stunting prevention. Thus, this activity is very useful in providing information about how to prevent and reduce the incidence of stunting. It is hoped that this activity will be carried out at SD Negeri 060919, Kec. Medan Sunggal, Medan City to pay more attention to the nutritional intake of mothers and children, so that the incidence of stunting in Indonesia is reduced.